Is it possible to identify ancient wine production using biomolecular approaches?. Issue 1 (1st January 2020) - Drieu, Léa; Rageot, Maxime; Wales, Nathan; Stern, Ben; Lundy, Jasmine; Zerrer, Maximilian; Gaffney, Isabella; Bondetti, Manon; Spiteri, Cynthianne; Thomas-Oates, Jane; Craig, Oliver E.
ABSTRACT: Chemical analysis of archaeological artefacts is used with increasing regularity to understand how wine was produced, traded, and consumed in the past and to shed light on its antiquity. Based both on an extensive review of the published literature and on new analyses, here we critically evaluate the diverse range of methodological approaches that have been used for wine identification. Overall, we conclude that currently none of the proposed chemical 'biomarkers' for wine provide unequivocal evidence. Nevertheless, valid interpretations may be offered if systematically supported by additional contextual data, such as archaeobotanical evidence. We found the extraction and detection method to be particularly crucial for successful identification. We urge the use of controls and quantification to rule out false positives. DNA sequencing offers potential for identifying wine and provides much higher taxonomic resolution, but work is needed to determine the limits of DNA survival on artefacts.